Accrochage 5. (Paris : Andrée Stassart, 1973)
Fang, Bieri ; Blake, Peter ; Braque, Georges ; Ernst, Max ; Richard ; Renoir, Auguste ; Hamilton, Richard ; Marechal, Jacques Le ; Miro, Joan ; Picasso, Pablo ; Pollock, Jackson ; Warren, Michel
Accrochage 5, Andrée Stassart, Paris, décembre 1973
boek